The Role of Cloud Computing Technology in Supporting Educational Accessibility and Scalability - Loebis, Iin Almeina; Mustofa, Muhammad; Arifin, Syaadiah; Angglena, Melly; Salim, Yeffriansjah (Journal International of Lingua and Technology, 2024)
Education is very important for human life. Many of them are vying for the best education in the world to guarantee a better future. The thing that is very concerned about in Education is learning and also the right method of teaching, because that way it can give birth to a competitive and quality generation. One of them is the role of cloud computing technology, which is a combination of the use of computer technology and internet-based development. A way or method that makes it easy for users to access information without knowing what is in it, being expert with it or having control over it. Cloud computing is an important technology that has helped many institutions and schools use distance learning, and can support Education's accessibility and scalability. The purpose of this study is to determine the role of cloud computing technology in increasing the accessibility and scalability of more advanced education and being able to create a generation that is highly competitive and virtuous. The method used in this study uses a quantitative method by distributing questionnaires to respondents as many as 15 statements about the use of cloud computing technology in education. The results of this study proved to be a very effective role for cloud computing technology in improving education, because this technology can increase students' interest in learning and make them enthusiastic in learning, so as to create an interactive learning atmosphere. The implication of this latest technology is to make learning more interesting and easily accessible anytime and anywhere by students. Assignments can be collected online by utilizing various supporting educational platforms and application delivery of subject matter.